Functional and Structural Consequences of Nine CYP21A2 Mutations Ranging from Very Mild to Severe Effects - Débora de Paula Michelatto; Leif Karlsson; Ana Letícia Gori Lusa; Camila D’Almeida Mgnani Silva; Linus Joakim Östberg; Bengt Persson; Gil Guerra-Júnior; Sofia Helena Valente de Lemos-Marini; Michela Barbaro; Maricilda Palandi de Mello; Svetlana Lajic (International Journal of Endocrinology)
We present the functional and structural effects of seven novel (p.Leu12Met, p.Arg16Cys, p.Ser101Asn, p.Ser202Gly, p.Pro267Leu, p.Gln389_Ala391del, and p.Thr450Met) and two previously reported but not studied (p.Ser113Phe and p.Thr450Pro) CYP21A2 mutations. Functional analyses were complemented with in silico prediction of mutation pathogenicity based on the recently crystallized human CYP21A2 structure. Mutated proteins were transiently expressed in COS-1 cells and enzyme activities towards 17-hydroxyprogesterone and progesterone were determined. Residual enzyme activities between 43% and 97% were obtained for p.Arg16Cys, p.Ser101Asn, p.Ser202Gly, p.Pro267Leu, and p.Thr450Met, similar to the activities of the well-known nonclassic mutations p.Pro453Ser and p.Pro482Ser, whereas the p.Leu12Met variant showed an activity of 100%. Conversely, the novel p.Ser113Phe, p.Gln389_Ala391del, and p.Thr450Pro mutations drastically reduced the enzyme function below 4%. The Km values for all novel variants were in the same order of magnitude as for the wild-type protein except for p.The450Met. The maximum velocity was decreased for all mutants except for p.Leu12Met. We conclude that p.Leu12Met is a normal variant; the mutations p.Arg16Cys, p.Ser101Asn, p.Ser202Gly, p.Pro267Leu, and p.Thr450Met could be associated with very mild nonclassic CAH, and the mutations p.Ser113Phe, p.Gln389_Ala391del, and p.Thr450Pro are associated with classic CAH. The obtained residual activities indicated a good genotype-phenotype correlation.